Breaking the frames : populism and prestige in comics studies - Singer, Marc (World comics and graphic nonfiction series., 2018)
"Comics studies has reached a crossroads. Graphic novels have never received more attention and legitimation from scholars, but new canons and new critical discourses have created tensions within a field built on the populist rhetoric of cultural studies. As a result, comics studies has begun to cleave into distinct camps--based primarily in cultural or literary studies--that attempt to dictate the boundaries of the discipline or else resist disciplinarity itself. The consequence is a growing disconnect in the ways that comics scholars talk to each other--or, more frequently, do not talk to each other or even acknowledge each other's work. Breaking the Frames: Populism and Prestige in Comics Studies surveys the current state of comics scholarship, interrogating its dominant schools, questioning their mutual estrangement, and challenging their propensity to champion the comics they study. Marc Singer advocates for greater disciplinary diversity and methodological rigor in comics studies, making the case for a field that can embrace more critical and oppositional perspectives. Working through extended readings of some of the most acclaimed comics creators--including Marjane Satrapi, Alan Moore, Kyle Baker, and Chris Ware--Singer demonstrates how comics studies can break out of the celebratory frameworks and restrictive canons that currently define the field to produce new scholarship that expands our understanding of comics and their critics."--Provided by publisher